A study of cutaneous adverse drug reactions at a tertiary center in Jammu, India - Rohini Sharma; Devraj Dogra; Naina Dogra (Wolters Kluwer Medknow Publications, 2015)
Aim: The aim was to study various morphological patterns of cutaneous adverse drug reactions (CADRs) and identify the culprit drug or drugs by establishing a causal link using Naranjo adverse drug reaction probability scale. Materials and Methods: The study was carried out between November 2010 and November 2011 at the Department of Dermatology, Government Medical College, Jammu. A total of 150 patients with CADR reporting to the dermatology department or referred from other departments were evaluated. Detailed history, clinical examination, hematological, and biochemical investigations were recorded. The venereal disease research laboratory test, HIV (ELISA), and histopathological examination were done wherever indicated. Results: A total of 150 patients were evaluated after applying the inclusion and exclusion criteria. The mean age of the patients with CADRs was 33.26 years. A majority of patients (30.6%) were in the age group of 21-30 years. The male to female ratio was 1.7:1.2. The most common CADRs were fixed drug eruption in 33.3% of patients followed by urticaria in 17.3%, and maculopapular rash in 13.3%. The most common classes of drugs implicated were antimicrobials in 40% of patients followed by nonsteroidal antiinflammatory drugs in 35.3%. The Naranjo adverse drug reaction probability scale indicated probable association of 77.3%, highly probable association of 12.6%, and 1% possible association with the implicated drugs. Conclusion: The pattern of CADRs and the drugs causing them is remarkably different in our population. Knowledge of these drug reactions, their causative drugs, and prognostic indicators is essential for the clinician.